Shirkah al-Mufawadah or equitable partnership in Islamic commercial law: a comparative analysis - Sadique, Muhammad Abdurrahman (Zes Rokman Resources, 2016)
Shirkah al-‛aqd or contractual partnership is generally divided in to four distinct types by most jurists of Islamic law, with some difference among them as to which of these can be held permissible and the conditions thereof. Out of these types, shirkah al-mufawadah or equitable partnership has been the subject of a lively discussion as to its nature andvalidity, where the Hanafi school has upheld it being a valid form of contractual partnership, in its specific form as described by them. However, they have conceded that its practical existence is rare. The current paper undertakes an analysis of the essential nature of sharikah al-mufawadah in the scheme of Islamic commercial partnerships. How the major schools of Islamic law have perceived the nature and conditions of this particular form of contractual partnership among the other types is discussed in detail, together with comparing the rationale behind them as expounded by Muslim jurists.